2017
DOI: 10.1016/j.egja.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesia by epidural magnesium sulphate versus fentanyl as adjuvant to levobupivacaine in geriatric spine surgeries. Randomized controlled study

Abstract: (2017) Evaluation of analgesia by epidural magnesium sulphate versus fentanyl as adjuvant to levobupivacaine in geriatric spine surgeries. Randomized controlled study, Egyptian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…We found that many studies did not adequately report randomization methods. Five studies did not describe the generation of random sequences in detail [12,14,15,19,22], two studies did not describe the methods of allocation concealment [17,18], three studies did not describe whether the anaesthetists were blind for this study design [14,15,20] and four studies did not report in detail their blind assessment of the outcomes [14,15,20,21]. Only one studies reported clinical trials registration [12] and we were not clear about the risk of selective outcome reporting bias.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that many studies did not adequately report randomization methods. Five studies did not describe the generation of random sequences in detail [12,14,15,19,22], two studies did not describe the methods of allocation concealment [17,18], three studies did not describe whether the anaesthetists were blind for this study design [14,15,20] and four studies did not report in detail their blind assessment of the outcomes [14,15,20,21]. Only one studies reported clinical trials registration [12] and we were not clear about the risk of selective outcome reporting bias.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search identified 4392 studies totally and 112 references from CENTRAL, 2481 references from MEDLINE (OvidSP), and 1799 studies from Embase (Ovidsp). Eleven studies fulfilled our inclusion criteria after screening [12][13][14][15][16][17][18][19][20][21][22]. The details of retrieval was shown in Fig.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations